Pure endoscopic endonasal treatment of acromegaly; classification, remission rates, factors affecting remission, and complications (Annals of Medical Research, 2023)
Aim: This study aims to evaluate the effectiveness of the pure endoscopic endonasal transsphenoidal (PEET) approach in treating acromegaly, focusing on remission criteria set by the 2002 and 2010 consensus guidelines. It also seeks to identify variables that affect remission and to analyze early postoperative IGF-1 levels 24 hours after surgery to determine their predictive value for remission.Materials and Methods: The study retrospectively reviewed the medical records of 129 acromegaly patients who underwent the PEET (Pure Endoscopic Endonasal Transsphenoidal) surgical approach between November 2010 and March 2016 at Ankara Numune Training and Research Hospital. Out of these, 124 patients with complete follow-up and laboratory data were included in the analysis. The study evaluated a range of variables including patients' symptoms, pre- and postoperative GH and IGF-1 levels, imaging results, and remission statuses based on the 2002 and 2010 consensus guidelines. Inclusion criteria for the study required patients to have specific preoperative and postoperative data and a minimum follow-up duration of at least 6 months.Results: The study found statistically significant differences between the remission rates based on the 2002 and 2010 consensus criteria for acromegaly, with a 73.4% remission rate under the 2002 criteria and a 65.3% remission rate under the 2010 criteria (p=0.002). Multivariate logistic regression analysis indicated that the atypical nature of the adenoma (p=0.018) and surgical intervention due to recurrence (p=0.028) were significant negative factors affecting cure rates. The study also identified that advanced stages in Hardy Wilson (p=0.008) and Knosp (p
Keywords: Acromegaly; Endoscopic; Remission; Cure